Imaging the Response to DNA Damage in Heterochromatin Domains - Chansard, Audrey; Pobega, Enrico; Caron, Pierre; Polo, Sophie E. (Frontiers in Cell and Developmental Biology, 2022)
The eukaryotic genome is assembled in a nucleoprotein complex called chromatin, whose organization markedly influences the repair of DNA lesions. For instance, compact chromatin states, broadly categorized as heterochromatin, present a challenging environment for DNA damage repair. Through transcriptional silencing, heterochromatin also plays a vital role in the maintenance of genomic integrity and cellular homeostasis. It is thus of critical importance to decipher whether and how heterochromatin affects the DNA damage response (DDR) to understand how this chromatin state is preserved after DNA damage. Here, we present two laser micro-irradiation-based methods for imaging the DDR in heterochromatin domains in mammalian cells. These methods allow DNA damage targeting to specific subnuclear compartments, direct visualization of the DDR and image-based quantification of the repair response. We apply them to study DNA double-strand break repair pathways in facultative heterochromatin and the repair of UV photoproducts in constitutive heterochromatin. We discuss the advantages and limitations of these methods compared to other targeted approaches for DNA damage induction.